Respuesta :

Answer:

see explanation

Step-by-step explanation:

Simplify the radical

[tex]\frac{U}{\frac{1}{f}+\frac{1}{g}  }[/tex]

= [tex]\frac{U}{\frac{g+f}{fg} }[/tex]

= [tex]\frac{Ufg}{g+f}[/tex]

Square both sides

T² = [tex]\frac{Ufg}{g+f}[/tex] ( multiply both sides by (g + f) )

T²(g + f) = Ufg ( distribute left side )

T²g + T²f = Ufg ← subtract Ufg from both sides

T²g - Ufg + T²f = 0 ← subtract T²f from both sides

T²g - Ufg = - T²f ← factor out g from each term on the left side

g(T² - Uf) = - T²f ← divide both sides by (T² - Uf)

g = - [tex]\frac{T^2f}{T^2-Uf}[/tex] = [tex]\frac{T^2f}{Uf-T^2}[/tex]